1993
DOI: 10.1093/nar/21.10.2331
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structures and transcription of rDNA in yeastSaccharomyces cerevisiae

Abstract: The chromatin structure of yeast ribosomal DNA was analyzed in vivo by crosslinking intact cells with psoralen. We found that in exponentially growing cultures the regions coding for the 35S rRNA precursor fall into two distinct classes. One class was highly accessible to psoralen and associated with nascent RNAs, characteristic for transcriptionally active rRNA genes devoid of nucleosomes, whereas the other class showed a crosslinking pattern indistinguishable from that of bulk chromatin and was interpreted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
310
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(328 citation statements)
references
References 37 publications
17
310
1
Order By: Relevance
“…Whereas early analyses based on psoralen accessibilities in rDNA led to the conclusion that actively transcribed rRNA genes are devoid of nucleosomes (Dammann et al 1993), more recent data suggest that active rDNA has nucleosomal structure (Jones et al 2007). We reasoned that ChEC could give more insights into the association of histone molecules with Pol I-transcribed loci.…”
Section: Actively Transcribed Rdna Is Largely Devoid Of Histone Molecmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas early analyses based on psoralen accessibilities in rDNA led to the conclusion that actively transcribed rRNA genes are devoid of nucleosomes (Dammann et al 1993), more recent data suggest that active rDNA has nucleosomal structure (Jones et al 2007). We reasoned that ChEC could give more insights into the association of histone molecules with Pol I-transcribed loci.…”
Section: Actively Transcribed Rdna Is Largely Devoid Of Histone Molecmentioning
confidence: 99%
“…The characteristic cross-linking pattern of the f-band visualized by electron microscopy suggested that the DNA had been assembled into nucleosomes in the living cell (Dammann et al 1993). Furthermore, it was demonstrated that nascent rRNA is selectively associated with the heavily psoralen-cross-linked s-band (Conconi et al 1989;Dammann et al 1993), leading to the conclusion that this (presumably) nucleosome-free fraction of rDNA is actively transcribed in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A 3.7 kb XbaI fragment of rDNA from plasmid pSZ26 (Dammann et al, 1993) was used as loading control. Hybridization and quantification were carried out as described elsewhere (Aranda et al, 2002).…”
Section: Rna Analysismentioning
confidence: 99%
“…Indeed, active transcription poses a problem for condensin's ability to facilitate segregation of sister chromatids within the nucleolus (Tomson et al, 2006;Wang et al, 2006). However, only half of the rDNA copies are transcriptionally active (Dammann et al, 1993;Dammann et al, 1995;French et al, 2003), and therefore condensin likely utilizes the existence of repeats silent for PolI transcription to mediate segregation of the nucleolus. This theory of compartmentalization between transcription and segregation function in rDNA has been substantiated in the recent study (Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%